Modernisasi Propesionalisme Guru Agama Kristen - Armela Nababan; Agriva Pandiangan; Edelwis Pardosi; Enjelina Enjelina; Hesty Sinaga; Lenny lubis; Hisardo Sitorus (Pusat riset dan Inovasi Nasional, 2025)
That Christian Religious Education teachers update their professionalism and competencies to ensure that Christian education remains relevant, effective, and transformative. This study aims to analyze the modernization of the professionalism of Christian Religious Education teachers, including the integration of spirituality with modern pedagogical approaches and strategies for developing teacher competencies in addressing the challenges of the digital generation. The study employs a descriptive qualitative approach, collecting data through literature review from books, journals, notes, and relevant reports, and presenting the findings in a narrative form. The results show that the modernization of teacher competencies involves the development of pedagogical, personal, social, spiritual, and professional competencies, with the ability to integrate spirituality, technology, and modern teaching methods such as collaborative and digital learning to create contextual, engaging, and transformative learning experiences. In conclusion, the modernization of professionalism among Christian Religious Education teachers is an urgent necessity to enable teachers to deliver God’s Word in a relevant manner, shape students’ character and spirituality, and enhance the effectiveness of Christian education through mastery of holistic and collaborative competencies.